β2-adrenergic receptor regulates ER-mitochondria contacts - Youngshin Lim (Nature Portfolio, 2021)
Abstract Interactions between the endoplasmic reticulum (ER) and mitochondria (Mito) are crucial for many cellular functions, and their interaction levels change dynamically depending on the cellular environment. Little is known about how the interactions between these organelles are regulated within the cell. Here we screened a compound library to identify chemical modulators for ER-Mito contacts in HEK293T cells. Multiple agonists of G-protein coupled receptors (GPCRs), beta-adrenergic receptors (β-ARs) in particular, scored in this screen. Analyses in multiple orthogonal assays validated that β2-AR activation promotes physical and functional interactions between the two organelles. Furthermore, we have elucidated potential downstream effectors mediating β2-AR-induced ER-Mito contacts. Together our study identifies β2-AR signaling as an important regulatory pathway for ER-Mito coupling and highlights the role of these contacts in responding to physiological demands or stresses.